Motivasi Ibu dalam Penggunaan KB IUD di Puskesmas Pakuan Baru Kota Jambi - NOFRAN PSIKOLOGI; Nurfitriani Nurfitriani (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2017)
INTRODUCTION Family Planning (FP) is one of the preventive health care of the most basic and foremost for women, these services must be provided to women by combining and meet the needs of the major reproductive health services and others, also responsive to the different stages of a woman's reproductive life. IUD is one of modern contraceptives. An intrauterine device that is designed in such a way that is placed in the uterine cavity as contraception hinders efforts complicate egg fertilization and implantation in the uterus. METHOD The research is a descriptive study using cross sectional design is to describe the variables studied. Population in this research are acceptors which totaled 286 people. With a sample of 73 people where the sampling technique accidental sampling, then the data is processed by univariate analysis. RESULT Based on the results of the study respondents from 73 respondents obtained as many as 29 (39.7%) of respondents that have a high motivation to use contraceptives and as many as 44 (60.3%) of respondents who have low motivation to use IUD in Puskesmas Pakuan Baru Jambi City 2015. CONCLUSIONS AND RECOMENDATIONS Expected for the Acceptor KB to always pay attention and check the health of the use of birth control, family planning acceptors have to motivate yourself to get knowledge about the usage KB is good and right Keywords: Motivation, use IUD